2006
DOI: 10.1097/01.mbc.0000214710.19116.40
|View full text |Cite
|
Sign up to set email alerts
|

Fondaparinux as anticoagulant in a pregnant woman with heparin allergy

Abstract: We report a patient who had a history of deep vein thrombosis in a previous pregnancy. She was treated with heparins without any reactions in the index pregnancy. Subsequently, when the patient became pregnant again, she developed an acute cutaneous reaction to the low molecular heparin enoxaparin 3 weeks after initiation of therapy. She developed a similar reaction to delteparin as well. She was therefore treated with warfarin until 36 weeks of gestation. Then she was treated with fondaparinux (Arixtra, Sanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…69 Although there have been a small number of reports of the successful use of this agent in pregnant woman, [70][71][72][73][74][75][76] most of these involve second trimester or later exposure. Thus, the quality of evidence regarding supporting use of fondaparinux in pregnancy is very low.…”
Section: Pentasaccharide Exposure In Uteromentioning
confidence: 99%
“…69 Although there have been a small number of reports of the successful use of this agent in pregnant woman, [70][71][72][73][74][75][76] most of these involve second trimester or later exposure. Thus, the quality of evidence regarding supporting use of fondaparinux in pregnancy is very low.…”
Section: Pentasaccharide Exposure In Uteromentioning
confidence: 99%
“…Fondaparinux is an indirect factor Xa inhibitor with the largest collection of case-based data in pregnancy. [48][49][50][51][52][53][54] Two direct factor Xa inhibitors, argatroban and lepirudin, have published human data in pregnancy. [55][56][57] Fondaparinux is recommended by the American College of Obstetrics and Gynecology for anticoagulation in the setting of heparin-induced thrombocytopenia or other heparin allergy.…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…Although it has been shown that transplacental passage can occur resulting in low measurable FXa activity in cord blood [11], no adverse outcomes in pregnancy have been reported in these four women. The other six separately published cases reported no adverse events to the mother or child [6][7][8][9][10]. In our hospital, experience with fondaparinux as an alternative in pregnant women has accumulated.…”
mentioning
confidence: 99%
“…Fondaparinux has been extensively studied for use in surgery prophylaxis and treatment of thromboembolic diseases [5]. However, data on the use of fondaparinux in pregnancy is limited to animal models and a few case reports [6][7][8][9][10]. Although it has been shown that transplacental passage can occur resulting in low measurable FXa activity in cord blood [11], no adverse outcomes in pregnancy have been reported in these four women.…”
mentioning
confidence: 99%
See 1 more Smart Citation